Anastomotic Leakages after Surgery for Gastroesophageal Cancer: A Systematic Review and Meta-Analysis on Endoscopic versus Surgical Management - Azevedo,Isabel (2023)
Abstract Introduction: With the increase of esophageal and gastric cancer, surgery will be more often performed. Anastomotic leakage (AL) is one of the most feared postoperative complications of gastroesophageal surgery. It can be managed by conservative, endoscopic (such as endoscopic vacuum therapy and stenting), or surgical methods, but optimal treatment remains controversial. The aim of our meta-analysis was to compare (a) endoscopic and surgical interventions and (b) different endoscopic treatments for AL following gastroesophageal cancer surgery. Methods: Systematic review and meta-analysis, with search in three online databases for studies evaluating surgical and endoscopic treatments for AL following gastroesophageal cancer surgery. Results: A total of 32 studies comprising 1,080 patients were included. Compared with surgical intervention, endoscopic treatment presented similar clinical success, hospital length of stay, and intensive care unit length of stay, but lower in-hospital mortality (6.4% [95% CI: 3.8-9.6%] vs. 35.8% [95% CI: 23.9-48.5%]. Endoscopic vacuum therapy was associated with a lower rate of complications (OR 0.348 [95% CI: 0.127-0.954]), shorter ICU length of stay (mean difference −14.77 days [95% CI: −26.57 to −2.98]), and time until AL resolution (17.6 days [95% CI: 14.1-21.2] vs. 39.4 days [95% CI: 27.0-51.8]) when compared with stenting, but there were no significant differences in terms of clinical success, mortality, reinterventions, or hospital length of stay. Conclusions: Endoscopic treatment, in particular endoscopic vacuum therapy, seems safer and more effective when compared with surgery. However, more robust comparative studies are need-ed, especially for clarifying which is the best treatment in specific situations (according to patient and leak characteristics).